Studying Cart Abandonment, Online Purchasing Behavior, Influences and Customer Preferences - Mythili, R (Ushus Journal of Business Management, 2024)
Cart abandonment remains a significant challenge in e-commerce, leading to lost revenue and hindering business growth. This study investigates the multifaceted role of online marketing strategies in influencing cart abandonment rates, with a specific focus on the often-overlooked contribution of Search Engine Optimization (SEO). Through [mention research methodology], the study analyzes how various online marketing tactics, particularly SEO practices, impact consumer behavior and purchase decisions, ultimately influencing cart abandonment rates. The findings reveal valuable insights into optimizing online marketing strategies to address cart abandonment challenges and enhance e-commerce success.This paper investigates the impact of online marketing strategies on cart abandonment rates in e-commerce, exploring the specific role of search engine optimization (SEO) in influencing consumer behavior and purchase decisions.